2022
DOI: 10.1021/acscatal.2c03996
|View full text |Cite
|
Sign up to set email alerts
|

Radical NHC Catalysis

Abstract: Radical/radical cross-coupling reactions represent an efficient and straightforward approach for the construction of chemical bonds and accordingly have drawn increasing attention over the past decades. In order to achieve synthetically useful transformations, a persistent radical should be coupled with a transient radical in accordance with the persistent radical effect (PRE). However, known transient radicals outnumber by far the known types of free persistent radicals, which limits the widespread applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
77
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 189 publications
(77 citation statements)
references
References 122 publications
0
77
0
Order By: Relevance
“…N-heterocyclic carbenes (NHCs) 9 could stabilize acyl radicals 10 and open a new avenue for single-electron-transfer (SET)-mediated radical acylation chemistry. 11 Since the pioneering works of Studer 12 and Ohmiya, 13 a elegant progress has been achieved in NHC-involved cross-couplings of ketyl radicals with O-centered radicals, 12 alkyl radicals, 13–18 and highly active allene radicals 19 by employing aldehydes or derivatives of carboxylic acid (Scheme 1b). The attachment of NHCs could modulate the stability of transient acyl radicals to persistent ones, which may offer the opportunity for radical acylation of allyl radicals.…”
Section: Introductionmentioning
confidence: 99%
“…N-heterocyclic carbenes (NHCs) 9 could stabilize acyl radicals 10 and open a new avenue for single-electron-transfer (SET)-mediated radical acylation chemistry. 11 Since the pioneering works of Studer 12 and Ohmiya, 13 a elegant progress has been achieved in NHC-involved cross-couplings of ketyl radicals with O-centered radicals, 12 alkyl radicals, 13–18 and highly active allene radicals 19 by employing aldehydes or derivatives of carboxylic acid (Scheme 1b). The attachment of NHCs could modulate the stability of transient acyl radicals to persistent ones, which may offer the opportunity for radical acylation of allyl radicals.…”
Section: Introductionmentioning
confidence: 99%
“…1a). 5–17 However, current KR studies are primarily addressing racemic substrates having each just one chiral center, owing to the operational constraints of constructing substrates with multiple chiral centers and enriching optically pure multichiral compounds, 18 and there have been very few reports on KR utilizing inactive groups distant from the chiral atoms. 19,20…”
Section: Introductionmentioning
confidence: 99%
“…N-Heterocyclic carbenes (NHCs) are well-known as nucleophilic organocatalysts for the umpolung of aldehydes via Breslow intermediates . Moving from traditional ionic chemistry logic to a radical approach, recent electrochemical and methodological studies , revealed that the reduction potential of deprotonated Breslow intermediate A was sufficiently negative to perform single electron transfer (SET) with various single electron acceptors, such as TEMPO, nitro compounds, and polyhalides , (Figure C). Pioneering studies from Ohmiya’s group reported NHC-catalyzed radical decarboxylative coupling of aldehydes with redox-active esters, allowing for the rapid assembly of functionalized ketones .…”
Section: Introductionmentioning
confidence: 99%